Perceived Usefulness and Ease of Use of Gpt Technology in Enhancing Staff and Students Creativity in Management and Social Science - Oyetola Oyelakun; Oluseyanu, Olamide (International Journal of Scientific Research and Management (IJSRM), 2024)
The reality of education today includes addressing the digital transformation affecting universities and other educational institutions. This study investigates the relationship between generative pre-trained transformer (GPT) technology and the perceived enhancement of creativity among students and academic staff in the management and social science disciplines. Methodologically, the study adopted a survey research method with the aim of analyzing data collected from a statistically sampled 90 respondents from all departments within the Faculty of Management and Social Sciences. The responses collected were analyzed using partial least squares structural equation modeling. The results revealed a significant association between perceived usefulness, perceived ease of usage of GPT technology, and creativity. The study concluded that though the use of GPT technology enhances learning in that it helps to improve creativity in students and lecturers, its weak influence shows that it doesn’t have the monopoly of enhancing creativity in lecturers and students without other measures put in place to enhance creativity.